The Role of Social Media Marketing with TikTok in Generation Z: A Study on the Choice of Fitness Centers by Generation Z in Ambon, Indonesia - Tubalawony, Jacsy (HM Publisher, 2023)
TikTok is a very popular platform among generation Z, who is often the main target in the fitness industry. Generation Z is very active on TikTok and uses the platform for inspiration on health, fitness and an active lifestyle. TikTok is a short video-based platform that enables gyms to present engaging visual content. This study aimed to determine the role marketing with social media TikTok in generation Z: a study on the choice of fitness centers by generation Z in Ambon, Indonesia. This study is a quantitative approach and uses primary data obtained from a survey process using a questionnaire, where the survey process is carried out online. The independent variable in this study is the choice of the fitness center brand by the customer (Y). The dependent variables in this study are entertainment (X1), interaction (X2), trendy (X3), customization (X4), and electronic word-of-mouth (WOM) (X5). In conclusion, there is a relationship between the entertainment, interaction, customization, and electronic word-of-mouth social media dimensions of TikTok in influencing brand fitness center choice decisions for generation Z in Ambon, Indonesia.